Application of Project Management Methods Usable in the Implementation Phase from the Perspective of Selected Chemical Companies - Košťálová, Jana; Tetřevová, Liběna (Česká společnost průmyslové chemie, 2017)
The article deals with project management methods applicable in the implementation phase of the project (Project Percent Complete Method, Structured Status Deviation, Milestone Trend Analysis and Earned Value Management) from the perspective of selected chemical companies operating in the Czech Republic. Its main objective is to provide a comprehensive view of the issue. In accordance with defined partial objectives, results were formulated and discussed using analysis, synthesis, comparison and deduction. The authors assessed the suitability of project management methods applicable in the implementation phase in terms of the type of projects. Their software support was evaluated. Their application by selected chemical companies in the Czech Republic was analyzed and evaluated. Strengths and limitations of these methods were summarized and recommendations formulated for their application in practice of chemical companies in the Czech Republic. For the evaluation, the authors used the binary scale as well as Project Management Methods and Tools Oriented Maturity Model. The article thus provides a unique and interesting perspective on the issue.
Aplikace metod řízení projektů využitelných v realizační fázi z pohledu vybraných chemických podniků
Keywords: project management; project life cycle; project management methods usable in the implementation phase; projektový management; životní cyklus projektu; metody projektového řízení uplatnitelné v implementační fázi